Rhythm and Vowel Quality in Accents of English - Schwartz, Geoff (Research in Language, 2010)
This paper will examine rhythmic differences among native and non-native accents of English, and report on a pilot experiment investigating a hypothesized interaction between rhythm and vowel quality. A new metric, % SteadyState, an acoustic measure that quantifies the purity of vowels, appears to capture rhythmic differences that have been reported among various native and non-native accents of English. In the tradition of other recently developed rhythm metrics, these findings suggest a link between rhythm and segmental phonology. Additionally, the perspective gained from this study may be beneficial to learners whose goal is native-like vowel quality, offering an understanding of the dynamic properties of English vowels.